Metastatic eccrine porocarcinoma - Calsina, David (2019)
We present the case of a 69-year-old male patient with tumor lesion in the left inguinal region, asymptomatic. The histopathological and immunohistochemical study was consistent with ecrine porocarcinoma. Upon imaging, nodal metastases in the iliac femoral, retroperitoneal and supraclavicular left region are evident. Ecrine porocarcinoma infiltration into supraclavicular ganglion is confirmed at histopathological study. Metastatic eccrine porocarcinoma is very rare. Surgical treatment is not possible in these cases. There is no standard systemic treatment, only case series with variable responses. Our patient received chemotherapy treatment with doxetacel with good clinical response to follow-up.